Action-Sentence Compatibility: The Role of Action Effects and Timing - Diefenbach, Christiane; Rieger, Martina; Massen, Cristina; Prinz, Wolfgang (Frontiers in Psychology, 2013)
Research on embodied approaches to language comprehension suggests that we understand linguistic descriptions of actions by mentally simulating these actions. Evidence is provided by the action-sentence compatibility effect (ACE) which shows that sensibility judgments for sentences are faster when the direction of the described action matches the response direction. In two experiments, we investigated whether the ACE relies on actions or on intended action effects. Participants gave sensibility judgments of auditorily presented sentences by producing an action effect on a screen at a location near the body or far from the body. These action effects were achieved by pressing a response button that was located in either the same spatial direction as the action effect, or in the opposite direction. We used a go/no-go task in which the direction of the to-be-produced action effect was either cued at the onset of each sentence (Experiment 1) or at different points in time before and after sentence onset (Experiment 2). Overall, results showed a relationship between the direction of the described action and the direction of the action effect. Furthermore, Experiment 2 indicated that depending on the timing between cue presentation and sentence onset, participants responded either faster when the direction of the described action matched the direction of the action effect (positive ACE), or slower (negative ACE). These results provide evidence that the comprehension of action sentences involves the activation of representations of action effects. Concurrently activated representations in sentence comprehension and action planning can lead to both priming and interference, which is discussed in the context of the theory of event coding.